Identification and Characterization of Antimicrobial Peptides with Therapeutic Potential - Guangshun Wang (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Antimicrobial peptides are key defense molecules adopted by all life forms to prevent infection. They also have other beneficial effects such as boosting immune response, anticancer, and wound healing. The antiviral effects of antimicrobial peptides have laid the foundations for developing new agents to combat seasonal Flu, HIV-1, RSV, Zika, and Ebola. This eBook is constructed to systematically deal with antimicrobial peptides from a variety of natural sources, including fungi, plants, and animals (insects, fish, amphibians, birds, and reptiles). It covers peptide discovery, antimicrobial activity, 3D structure, mechanisms of action and potential applications. Naturally Occurring Antimicrobial Peptides, an eBook published by the journal Pharmaceuticals, provides a helpful introduction to newcomers and refreshes the minds of veterans.